Lactose Malabsorption and Lactose Intolerance in Children with Inflammatory Bowel Diseases - Jasielska, Martyna (Gastroenterol Res Pract, 2019)
BACKGROUND: Insufficient vitamin D and calcium intake associated with the restricted intake of milk and dairy products can lead to poor health outcomes like malnutrition and abnormal bone mineralization. The aim of the study was to estimate the prevalence of primary and secondary lactose intolerance in children with IBD. METHODS: The study included 107 patients (mean age 14.07 ± 3.58 years; 46.7% boys) which includes 43 patients with Crohn's disease (CD), 31 with ulcerative colitis (UC), and 33 children with functional abdominal pain (AP-FGID). We analysed the result of the hydrogen breath test with lactose loading, two single nucleotide polymorphisms of the LCT gene (LCT-13910CC and LCT-22018GG). The results were analysed with MedCalc Statistical Software. RESULTS: Adult-type hypolactasia (ATH) was found in 31% of patients with IBD and 42.4% of AP-FGID (p = 0.2). Lactose malabsorption (LM) was found in 27.9% of patients with CD, in 22.6% with UC, and in 24.2% with AP-FGID (p = 0.8). Lactose intolerance (LI) was diagnosed in a similar percentage of patients in each group (p = 0.9). Secondary LI in IBD patients does not depend on the location, duration, and activity of the disease and the number of relapses (p > 0.05). The median time of lactose-free diet in CD was 10 months and in CU 24 months. CONCLUSIONS: The incidence of LI, LM, and ATH does not differ among children with IBD from the population.